Pengaruh Harga dan Promosi Digital terhadap Keputusan Pembelian Kredit Pemilikan Rumah (KPR) di Bank BJB Cabang Soreang - Zabila, Ajenk Putri; Perwito, Perwito (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of price and digital promotion carried out by the Soreang Branch of Bank BJB using a quantitative method with a descriptive approach. The method was chosen to describe what was observed in accordance with relevant facts and existing problems. The number of samples is 132 respondents and the population is 195. The results of this study are that digital prices and promotions can increase purchasing decisions for housing loans (KPR) at Bank BJB Soreang Branch. Keywords: price, digital promotion, purchase decision